Effect of ApoE4 Genotype on the Association Between Metabolic Phenotype and Subclinical Atherosclerosis in Postmenopausal Women - Intira Sriprasert (2019)
© 2019 Elsevier Inc. Metabolic profile and ApoE4 genotype have effects on coronary heart disease. We examined the interaction between these factors on subclinical atherosclerosis in postmenopausal women from the Early versus Late Intervention Trial with Estradiol (n = 497). Based on nine metabolic biomarkers (fasting blood glucose, insulin sensitivity, ketones, triglycerides, high-density lipoprotein, low-density lipoprotein, hemoglobin A1c, and blood pressure), K-means clustering categorized women into three distinct phenotypes: healthy, high blood pressure, and poor metabolic. ApoE4 genotype was classified as either ApoE4+ or ApoE4−. General linear models tested whether the cross-sectional association between metabolic phenotypes and common carotid intima media thickness (CIMT) differed by ApoE4 genotype. Mixed effects linear models evaluated the modifying role of ApoE4 genotype on the association of metabolic phenotype with CIMT progression over a median follow-up of 4.8 years. In cross-sectional analysis, ApoE4+ women with poor metabolic phenotype had the highest CIMT compared with all other groups. In ApoE4− women, CIMT was significantly lower in those classified as healthy compared with high blood pressure phenotype (p = 0.004). In ApoE4+ women, CIMT was significantly higher in those with poor metabolic phenotype compared with healthy (p = 0.0003) and high blood pressure (p = 0.001) phenotypes. These results indicate that metabolic phenotype had a negative effect on CIMT in women with ApoE4+ but not ApoE4− (interaction p = 0.001). These effects were not observed on CIMT progression in longitudinal analysis. In conclusion, ApoE4+ women are more likely to have higher levels of subclinical atherosclerosis if their metabolic phenotype is poor compared with ApoE4+ women without poor metabolic profile and ApoE4− women.